Factibilidad para la creación de una empresa de producción de hortalizas orgánicas en la hacienda Santa Margarita de Cotogchoa, cantón Rumiñahui, provincia de Pichincha - Amada Culqui, Mariana de Jesús (2015)
The main objective of the present study is the creation of a production and marketing company for organic vegetables with added value, in Santa Margarita de Cotogchoa hacienda, located Ruminahui, Pichincha province, taking advantage of the existing market for this type of product in the market of Santa Clara de Quito, and the production of organic vegetables from small-scale farmers in the Hacienda Santa Mariana de Jesus, who, through this company can meet current and future of these organic products demand. Which was first and foremost a market study that included the analysis of the demand for organic vegetables in the sector which includes the market of Santa Clara, through a sample of 355 families and the study of the supply through the productive study and its projection, twenty farmers of hacienda Santa Mariana de Jesus, who will actively participate in the company. As result of the diagnostic field and marketing, could see that there are favorable conditions for the development of the project, due to the climatic conditions of the area in production, fertility of the soil, of purity and quality-tested water sheds, proximity to the population, roads manufacturing them and skilled peasant family. Which indicates that the company promoted, will have direct and indirect beneficiaries, such as producers and consumers, and on the other hand the rural sector will be higher income, with respect for the environment, which not only improve the quality of life of rural families engaged in the agricultural enterprise, but its economic status. As for the engineering of the project, to determine the processes of organic horticulture, the size and location of the company, physical distribution and the individual designs of different crops that will be managed with family labour as well as of the financial study could be established, reflected its results positive indicators to existing as a going positive greater than one, an IRR of 23.7% which is higher than the rate of the credit of the national financial sector and a relationship benefit cost of 1.48 or greater than one. Financial indices that show us technically there is the feasibility of the project, since this financial information we were able to establish a positive project sensitivity, which does not affect the increase in costs by 1.5%. Concluding our study that there is a potential market in Barrio Santa Clara, sufficient for the consumption of the production and its projection of vegetables in the hacienda Santa Marianita de Jesus and viability for the project which will have a time of recovery of its investment there according to the financial study may develop in 3 years, 7 months and 24 days, which indicates that the time in which to recover the capital is acceptable. And may recommend the implementation of the project which was accepted after their socialization with farmers, who believes that it is alternative to develop better living conditions and economic beneficiaries.